INFLUENCE OF THE COMPOSITION OF THE MIXTURE AND THE TYPE OF PROCESSED FIBERS ON THE PHYSICAL PROPERTIES OF FABRICS (Multidisciplinary Journal of Science and Technology, 2024)
this article presents the results of studies to determine the physical properties of fabric obtained from various fibers and recycled fibrous waste. For this purpose, in production conditions, a sliver with a linear density of 5000 tex was obtained on a JFA-226 carding machine, and in the laboratory of the Department of Spinning Technology, slivers were also obtained in three versions on an HSR-1000 brand draw machine. To produce a twill weave fabric on a picanol loom, the warp threads were mixed with yarn consisting of 100% cotton, and the weft thread was mixed with yarn consisting of recycled fibers and the physical properties of the fabric were studied.